NATURAL RESOURCES FERULA VARIA (SCHRENK) TRAUTV. IN KONIMEKH DISTRICT OF NAVOI REGION (Scientific journal of the Fergana State University, 2024)
The article provides information on the natural raw material reserves of Ferula varia in the Kanimekh district of the Navoi region. The determination of natural, biological and operational reserves of the species was carried out according to the characteristics developed by Pupikina et al. (2019). In accordance with it, it was established that the mass of the volume of model specimens on an area of 10x10 is 103.57±0.44 g, and the shrinkage coefficient is 66.6±0.68%. It was found that the relative dry mass is 34.52±0.71 g. In accordance with the indicators, it was established that the average yield in the survey area (10x10) is 244.06±15.98 grams, the yield per 1 ha is 24.4±1.59 kg, and the possible harvest volume is 0.146 tons. As a result, it was established that in 2024 the possible volume of 0.511 tons of raw materials, out of an area of 40.0 hectares of Ferula varia resource value in the Kanimekh district.